Shape switching and tunable oscillations of adaptive droplets - Dullweber, Tim; Belousov, Roman; Autorino, Camilla; Petridou, Nicoletta I.; Erzberger, Anna (Physical review letters, 2025)
Living materials adapt their shape to signals from the environment, yet the impact of shape changes on signal processing and associated feedback dynamics remains unclear. We find that droplets with signal-responsive interfacial tensions exhibit shape bistability, excitable dynamics, and oscillations. The underlying critical points reveal novel mechanisms for physical signal processing through shape adaptation in soft active materials. We recover signatures of one such critical point in experimental data from zebrafish embryos, where it supports boundary formation.
Gesehen am 21.01.2026